2016
DOI: 10.1111/evj.12653
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and interobserver reliability estimates for identification and grading of upper respiratory tract abnormalities recorded in horses at rest and during overground endoscopy

Abstract: Observers were consistent in grading URT disorders. However, significant disparity in grading existed between observers for some conditions affecting reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 24 publications
5
25
1
Order By: Relevance
“…Arytenoid function was graded using the 7‐point Havemeyer scale and then reclassified into binary grades (grade < 3.1 or grade ≥ 3.1). For experienced clinicians, intraobserver agreement for the ordinal scale was substantial as reported by McGivney et al , and excellent for the binary scale. Interobserver agreement for experienced clinicians was substantial for the ordinal grades differing from McGivney et al who reported only fair agreement.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…Arytenoid function was graded using the 7‐point Havemeyer scale and then reclassified into binary grades (grade < 3.1 or grade ≥ 3.1). For experienced clinicians, intraobserver agreement for the ordinal scale was substantial as reported by McGivney et al , and excellent for the binary scale. Interobserver agreement for experienced clinicians was substantial for the ordinal grades differing from McGivney et al who reported only fair agreement.…”
supporting
confidence: 63%
“…For experienced clinicians, intraobserver agreement for the ordinal scale was substantial as reported by McGivney et al , and excellent for the binary scale. Interobserver agreement for experienced clinicians was substantial for the ordinal grades differing from McGivney et al who reported only fair agreement. However, McGivney et al found that agreement was better when using Krippendorph’s α (0.59) since this type of analysis considers the proximity of the different observers’ grades, indicating that some observers consistently graded higher or lower than other observers.…”
contrasting
confidence: 53%
See 1 more Smart Citation
“…This study by C.L. McGivney and colleagues in Ireland and Norway evaluated observer agreement in upper respiratory tract (URT) endoscopy for multiple URT disorders, during resting and overground endoscopy .…”
Section: Reliability Of Urt Endoscopic Gradingmentioning
confidence: 99%
“…Overground endoscopy (OGE) is now commonly used for diagnosis of upper respiratory tract (URT) disorders in horses during exercise [1][2][3][4][5][6]. However, variability in exercising endoscopy findings have been recognised to occur in association with different exercise intensities, head positions, tack and inter-observer variation in URT disorder grading [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%